Recommendations for Success in Forming and Maintaining a SoTL Community of Practice - du Plessis, Aletta M.; Schreck, Cornelia M.; Bisschoff, Christo A.; Coetzee, Dané; Kahts-Kramer, Samantha A.; Oosthuizen, Jacobus J. (Teaching and Learning Inquiry, 2025)
Scholarship of Teaching and Learning (SoTL) communities of practice (CoP) have emerged as collaborative learning environments that unite people with a shared interest. However, forming and maintaining a successful SoTL CoP can be challenging, requiring careful planning and execution. As academics, we encounter various universal problems and challenges in our teaching and learning practices, particularly in a discipline-focused environment. Researching these challenges is the obvious path to finding answers. However, many discipline-focused academics are unsure of where to begin or how to conduct research on their teaching and learning. As novice SoTL researchers, we established a SoTL CoP in 2021. We used Participatory Action Learning and Action Research (PALAR) principles to form and function our CoP. After two years of successfully maintaining our SoTL CoP, we analysed the data gathered during our meetings. We identified four main themes: Unity in diversity, maximising collaborative potential, nurturing collaboration, and navigating success. We used these themes to compile guidelines for successfully forming and maintaining a SoTL CoP. Implementing these guidelines within a discipline-focused environment will support the development of a collaborative and supportive environment for the advancement of SoTL practices. By prioritising these guidelines, a CoP can thrive, fostering a collaborative and cohesive community where members actively participate, share their expertise, and contribute to collective growth within SoTL. Photo created using DALLE-3, 2024.